GC-MS Studies in Ethyl acetate extract of Rare, Endemic Medicinal plant Crotalaria ramosissima - A Comparative Study - Gokila T,; Arul Sheeba Rani. M,; Sincy Joseph,; Anitha T,; Kiruthika S, (The Bioscan, 2026)
Gas chromatography mass spectrometry (GC-MS) analysis was carried out to investigate the phytochemical composition of the stem and root of Crotalaria ramosissima. The study revealed the presence of a diverse range of bioactive compounds, with 28 compounds identified in the stem ethyl acetate extract and 30 compounds detected in the root ethyl acetate extract. These compounds belong to various chemical classes such as alkaloids, flavonoids, terpenoids, fatty acids, and phenolic derivatives, which are known for their significant pharmacological activities. Many of the identified constituents exhibit potent antimicrobial, antioxidant and anti-inflammatory properties, suggesting their potential role in therapeutic applications. The variation in compound distribution between stem and root indicates differential biosynthesis and accumulation of metabolites in plant parts. The presence of these bioactive molecules supports the traditional medicinal use of Crotalaria ramosissima and highlights its importance as a promising source of natural drugs. This study provides a scientific basis for further investigation into the isolation, characterization, and biological evaluation of these compounds. Overall, the GC-MS profiling emphasizes the plant’s potential in pharmaceutical and nutraceutical development.